Anatrophic Nephrolithotomy for The Management of Large Complete Staghorn Calculi - Dongol, Udaya Man Singh; Bohora, Sandeep (Journal of Kathmandu Medical College, 2018)
Background: Complete staghorn calculus is a challenging issue in urological practice. Anatrophic nephrolithotomy is a major surgery frequently performed for a large complete staghorn calculus. Current endourological procedures like percutaneous nephrolithotomy or extracorporeal lithotripsy or retrograde intra renal surgery are less effective in the management of complete large staghorn calculi. Objectives: The objective of this study is to assess the safety and effi cacy of anatrophic nephrolithotomy in the management of complete large staghorn calculus diseases. Methodology: Total 25 adult patients with complete staghorn calculi from March 2012 to the fi rst week of Sept 2017 were included in the study and were evaluated for patient demography, operating time, blood transfusion rate, cold ischemia time, hospitalization duration, stone clearance rate and the complications. Results: Twenty five adult patients with the mean age of 36 years (26-73years) and the mean stone size of 50 mm (40- 65mm) underwent anatrophic nephrolithotomy. Fifteen were male patients and 10 female patients. The mean operating time was 156 minutes (130—210 minutes) and the cold ischemia time was 41 minutes (33-54 minutes). Six patients (24%) needed blood transfusion. The duration of hospital stay was 7.2 days (6–11 days). The stone clearance rate was 88 % at the time of discharge and 96 % at three month follow up. Conclusion: Anatrophic nephrolithotomy is a valid and useful approach and is a reasonable alternative in selected patients with complete large staghorn calculi. It can achieve high stone free rate with very low morbidity and low cost. Journal of Kathmandu Medical College, Vol. 6, No. 4, Issue 22, Oct.-Dec., 2017, Page: 140-144